Presence of sarcopenia does not affect the clinical results of balloon kyphoplasty for acute osteoporotic vertebral fracture - Shoichiro Ohyama (Nature Portfolio, 2021)
Abstract Sarcopenia has been associated with poor clinical outcomes in several diseases. Herein, the clinical results of balloon kyphoplasty (BKP) for acute osteoporotic vertebral fracture (OVF) treatment were assessed and compared between sarcopenia and non-sarcopenia patients. Sixty patients who underwent BKP for treatment of acute OVF with poor prognostic factors between April 2016 and September 2017 and were assessed for sarcopenia were enrolled. Clinical results (back pain on visual analogue scale [VAS]; short-form [SF] 36; vertebral deformity; activities of daily living levels; and incidence of adjacent vertebral fractures) were compared between the two groups at 6 months post-BKP. Data analysis revealed that back pain on VAS, SF-36 scores, and vertebral deformity improved from baseline to 6 months after BKP. Thirty-nine patients (65.0%) were diagnosed with sarcopenia and demonstrated a lower body mass index (21.2 vs. 23.3 kg/m2, p = 0.02), skeletal muscle mass index (5.32 vs. 6.55 kg/m2, p < 0.01), hand-grip strength (14.7 vs. 19.2 kg, p = 0.01), and bone mineral density of the femoral neck (0.57 vs. 0.76 g/cm2, p < 0.01) than those of patients without sarcopenia. However, no significant differences were observed in the clinical results between these groups. Therefore, BKP’s clinical results for the treatment of acute OVF are not associated with sarcopenia.